2015
DOI: 10.1007/s10048-015-0453-1
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of SIGMAR1 variant (rs4879809) segregating in a consanguineous Pakistani family showing amyotrophic lateral sclerosis without frontotemporal lobar dementia

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder affecting upper motor neurons in the brain and lower motor neurons in the brain stem and spinal cord, resulting in fatal paralysis. It has been found to be associated with frontotemporal lobar degeneration (FTLD). In the present study, we have described homozygosity mapping and gene sequencing in a consanguineous autosomal recessive Pakistani family showing non-juvenile ALS without signs of FTLD. Gene mapping was carried out in all recruited f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…5 Homozygous SIGMAR1 mutations cause juvenile or young-onset ALS with no cognitive deficit. [6][7][8] Here, we identified a novel SIG-MAR1 mutation together with a common, but damaging, singlenucleotide polymorphism in an ALS patient with the oldest-old onset.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…5 Homozygous SIGMAR1 mutations cause juvenile or young-onset ALS with no cognitive deficit. [6][7][8] Here, we identified a novel SIG-MAR1 mutation together with a common, but damaging, singlenucleotide polymorphism in an ALS patient with the oldest-old onset.…”
Section: Dear Editormentioning
confidence: 99%
“…However, one of these families was subsequently identified as positive for the C9orf72 mutation, suggesting that the SIGMAR1 mutation does not exclusively explain the etiology at least in this family . Homozygous SIGMAR1 mutations cause juvenile or young‐onset ALS with no cognitive deficit . Here, we identified a novel SIGMAR1 mutation together with a common, but damaging, single‐nucleotide polymorphism in an ALS patient with the oldest‐old onset.…”
mentioning
confidence: 98%
“…Instead, its nearest homolog is the yeast Δ8-Δ7 sterol isomerase, ERG2p, although the σ 1 receptor itself has no detectable isomerase activity 11 . Human genetic data have linked point mutants in σ 1 receptor to inherited motor neuron diseases [12][13][14] , and animal models implicate the receptor in Parkinson's disease 15 , addiction 16 , and pain 17 . A σ 1 receptor antagonist is currently in clinical trials for the treatment of neuropathic pain 7 , and agonists are in clinical trials for Alzheimer's disease 5 and ischemic stroke 6 .…”
mentioning
confidence: 99%
“…σ1R is highly expressed in motor neurons [ 1 , 27 ], and autosomal recessive loss-of-function mutations in σ1R are primarily associated with distal hereditary motor neuropathy [ 10 , 46 , 47 ], and ALS/FTLD [ 23 , 48 ]. In vitro studies have revealed aberrant subcellular distribution of σ1R E102Q in NSC34 cells and have shown that cells expressing the mutant protein are more prone to apoptosis induced by ER stress than those expressing the WT protein [ 25 ].…”
Section: Discussionmentioning
confidence: 99%